Factors that influence scope of practice of the five largest health care professions in Australia: a scoping review - Desmond Wiggins; Aron Downie; Roger M. Engel; Benjamin T. Brown (BMC, 2022)
Abstract Introduction A well-functioning health system delivers quality services to all people when and where they need them. To help navigate the complex realm of patient care, it is essential that health care professions have a thorough understanding of their scope of practice. However, a lack of uniformity regarding scope of practice across the regulated health professions in Australia currently exists. This has led to ambiguity about what comprises scope of practice in some health care professions in the region. Objective The objective of this review was to explore the literature on the factors that influence scope of practice of the five largest health care professions in Australia. Methods This study employed scoping review methodology to document the current state of the literature on factors that influence scope of practice of the five largest health care professions in Australia. The search was conducted using the following databases: AMED (Allied and Complementary Medicine Database), CINAHL (Cumulative Index to Nursing and Allied Health Literature), Cochrane Library, EMBASE (Excerpta Medica Database), MANTIS (Manual, Alternative and Natural Therapy Index System), MEDLINE, PubMed, and SCOPUS. Additional data sources were searched from Google and ProQuest. Results A total of 12 771 publications were identified from the literature search. Twenty-three documents fulfilled the inclusion criteria and were included in the final analysis. Eight factors were identified across three professions (nursing & midwifery, pharmacy and physiotherapy) that influenced scope of practice: education, competency, professional identity, role confusion, legislation and regulatory policies, organisational structures, financial factors, and professional and personal factors. Conclusion The results of this study will inform a range of stakeholders including the private and public arms of the healthcare system, educators, employers, funding bodies, policymakers and practitioners about the factors that influence scope of practice of health professions in Australia.